Distance Protection Solution for a Converter Controlled Microgrid - Dewadasa, J.; Ghosh, Arindam; Ledwich, G. (-, 2008)
Distance relay response in the presence of a converter dominated microgrid system has been analyzed in this paper. Converter structure and control mechanism are presented and a new method is proposed to limit fault currents in faulted phase/phases by reducing the converter output voltage. A method of analyzing unsymmetrical supply voltage using symmetrical component theory is proposed, where it has been assumed that voltage source converter (VSC) supplies unbalanced voltages in the event of a fault. Performance of distance relays with Mho characteristics are evaluated in a radial distribution feeder for both phase and earth unbalanced faults. The results are validated through PSCAD simulation and MATLAB calculations.